Advantages and Directions of Electronic Interaction in Web-Learning - Ekaterina A. Alexandrova; Stepan I. Akhmetov; Mohamed R. Attia (Saratov State University, 2020)
E-learning (web-learning) is a relatively new and actively developing form of education and a field of scientific research. The purpose of the research presented in the article is to describe the advantages of electronic interaction between a teacher and a student. The hypothesis of the research was that web-learning in different directions creates many options for effective interaction between students and teachers. We revealed potentially equal opportunities for web-learning; freedom of access (freedom to choose); flexibility (mobility) of training; ability to develop in tune with the times (cultural conformity); reduction in training fees; the ability to determine the criteria for assessing knowledge (objectivity); individualization of the choice of teaching aids (freedom). We demonstrated direction of electronic interaction: a) active interaction of a student and teachers with content: interaction of students with content; teacher interaction with contents; interaction of content with content; b) personal and social interaction with a teacher, parents and peers: interaction of a student with a teacher; student-student interaction; interaction between a teacher and a teacher; c) interaction with the educational organization in the process of navigation between the interfaces of their interaction: the interaction of a student with an interface; teacher interaction with an interface; interaction with programs, applications and sites; interaction of a student with himself/herself. We propose following indicators for determining the level of interaction efficiency in web-based training programs: availability, feedback, validity of the task. The use of various orientations of web-learning by a teacher in practice will allow to ensure individualization of the choice of teaching tools, objectivity, accessibility, feedback from a student, as well as freedom of access to information, flexibility (mobility) of training, the ability to develop in tune with the times.